Strategies for men’s engagement and its effectiveness in improving child health and immunization—a rapid review - Nabia, Sarah; Betron, Myra; Arlotti-Parish, Elizabeth; Varnauskas, Amanda; Nduka, Chinelo Cynthia; Pius, Angioha; Munro, Jean; Bagshaw, Katharine; Wonodi, Chizoba Barbara (Frontiers in Public Health, 2025)
IntroductionDespite widespread evidence and recognition that women bear the disproportionate burden of caregiving, there are major gaps in action geared towards equalizing this burden of care between men and women especially in the context of child health and immunization. The goal of this rapid review is to identify and summarize effective and promising strategies for men’s engagement in child health and immunization in low-and-middle-income countries (LMICs) and further categorize the strategies into its potential for gender transformative outcomes.MethodsWe searched PubMed, Embase and CINAHL databases for peer-reviewed literature and identified grey literature sources through key informant interviews. Twenty-seven papers and/or documents were included in the analysis. Data analysis was done through narrative synthesis, and results have been presented using the various levels of the socio-ecological model (SEM).ResultsMajority strategies were at the “intrapersonal” level of SEM and focused on individual education and awareness building through one-on-one or group communication approaches and practical training. Efficacy of these strategies was measured using various indicators such as knowledge and perception levels, paternal-infant attachment, biological marker levels, and paternal behavior. Joint / shared couples’ decision-making was the only gender transformative outcome reported in this review.DiscussionWe found gaps in community and policy level interventions, and provider-side interventions to positively influence men’s engagement in child health and immunization. Moreover, only two studies measured the strategies’ influence on improving immunization outcomes.ConclusionIt can be concluded there is a significant need for more evidence on gender-transformative approaches in child health and immunization programming in LMICs.